Civil Society Control over the Use of Digital Technologies in the Electoral Process in the Context of European Integration - Yurichuk, Yevheniia; Komolov, Artem (Mediaforum : Analytics, Forecasts, Information Management, 2023)
The digital revolution has changed the way we participate in democracy, in particular how we vote and participate in political discourse; however, it has also given rise to new types of electoral irregularities that can become a source of political crises and instability. The EU seeks to strengthen control over elections, their transparency and monitoring in order to maximise the democratic participation of citizens. Citizens’ digital participation in the election process can increase voter turnout, improve accuracy and efficiency, and ensure greater transparency and accountability. However, it is essential to ensure the safe and transparent use of digital technologies and that citizens have access to information and resources that will allow them to participate fully in the electoral process.Civil society plays a critical role in ensuring that elections are free, fair and transparent and in monitoring/observing the use of digital technologies in the electoral process. By providing oversight, observation, advocacy, and education of election participants, civil society can help ensure that the electoral process is accessible, fair, and reflective of the people’s will.